Relating (Un)acceptability to Interpretation. Experimental Investigations on Negation - Etxeberria, Urtzi; Tubau, Susagna; Deprez, Viviane; Borràs-Comes, Joan; Espinal, M. Teresa (Frontiers in Psychology, 2018)
Although contemporary linguistic studies routinely use unacceptable sentences to determine the boundary of what falls outside the scope of grammar, investigations far more rarely take into consideration the possible interpretations of such sentences, perhaps because these interpretations are commonly prejudged as irrelevant or unreliable across speakers. In this paper we provide the results of two experiments in which participants had to make parallel acceptability and interpretation judgments of sentences presenting various types of negative dependencies in Basque and in two varieties of Spanish (Castilian Spanish and Basque Country Spanish). Our results show that acceptable sentences are uniformly assigned a single negation reading in the two languages. However, while unacceptable sentences consistently convey single negation in Basque, they are interpreted at chance in both varieties of Spanish. These results confirm that judgment data that distinguish between acceptable and unacceptable negative utterances can inform us not only about an adult’s grammar of his/her particular language but also about interesting cross-linguistic differences. We conclude that the acceptability and interpretation of (un)grammatical negative sentences can serve linguistic theory construction by helping to disentangle basic assumptions about the nature of various negative dependencies.